Influence of blast hole shape and in-situ stress on blast damage evolution in granite by numerical simulation - Cunquan Wu; Fasheng Luo; Bin Li; Gaoyu Lin; Bo Hu; Xuefu Zhang; Mi Nie (Frontiers in Earth Science)
With the increasing development of deep underground engineering projects, under in-situ stress constraints, tunnel blasting excavation faces significant challenges in crack control. This study aimed to explore crack propagation patterns in rock blasting under varying in-situ stress conditions. Numerical models for single-hole and V-shaped slot blasting were developed using the ANSYS/LS-DYNA finite element platform, incorporating fluid-solid coupling. Six experimental groups with in-situ stress levels ranging from 0 to 10 MPa were analyzed to evaluate the effects on crushing zones, crack propagation, and overbreak/underbreak phenomena. Results showed that higher in-situ stress inhibits radial crack propagation, with cracks penetrating the surface at stress levels below 4 MPa. Increasing stress leads to reduced damage radius and volume, while V-shaped slots effectively alter stress fields and minimize overbreak. Under low stress, over-break is driven by circumferential cracks, whereas under higher stress, underbreak occurs and deepens. This research provides insights into optimizing blasting techniques to enhance rock fragmentation quality and minimize environmental impacts.